2009
DOI: 10.1152/jn.90483.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Divalent Cations on Spontaneous and Evoked Glycine Release From Spinal Interneurons

Abstract: The effects of Ca2+, Sr2+, and Ba2+ on spontaneous and evoked glycinergic inhibitory postsynaptic currents (mIPSCs and eIPSCs) were studied using the "synaptic bouton" preparation of rat spinal neurons and conventional whole cell recording under voltage-clamp conditions. In response to application of Ca2+-free solution, the frequency of mIPSC initially rapidly decreased to 40 approximately 50% of control followed by a gradual further decline in mIPSC frequency to approximately 30% of control. Once mIPSC freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 54 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Chronic treatment of rats with ethanol also increases mEPSC frequency and amplitude but does not affect evEPSC PPR (Stuber et al, 2008). It is possible that results from PPR and mESPC studies do not always agree because neurotransmitter release contributing to mEPSCs or mIPSCs can have Ca 2+ -dependent and Ca 2+ -independent components, and PPR results can reflect contributions from action potential- and Ca 2+ -dependent neurotransmitter release (Maeda et al, 2009). Given these considerations and caveats, we favor the interpretation that systemic exposure to nicotine increases glutamatergic synaptic plasticity via time-dependent effects on both pre- and post-synaptic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment of rats with ethanol also increases mEPSC frequency and amplitude but does not affect evEPSC PPR (Stuber et al, 2008). It is possible that results from PPR and mESPC studies do not always agree because neurotransmitter release contributing to mEPSCs or mIPSCs can have Ca 2+ -dependent and Ca 2+ -independent components, and PPR results can reflect contributions from action potential- and Ca 2+ -dependent neurotransmitter release (Maeda et al, 2009). Given these considerations and caveats, we favor the interpretation that systemic exposure to nicotine increases glutamatergic synaptic plasticity via time-dependent effects on both pre- and post-synaptic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that the precise molecular events underlying excitatory and inhibitory, and spontaneous and evoked neurotransmitter release, may be different. We have also seen differences between spontaneous and evoked release in their sensitivity of divalent cations, and had previously suggested that spontaneous and evoked glycine release in SDCN neurons involved Ca 2+ binding to different synaptotagmins (Maeda et al, 2009). Recent studies have now in fact indicated that > 95% spontaneous release is induced by Ca 2+ -binding to synaptotagmin 1 in murine cortical neurons (Xu et al, 2009), while synaptotagmins 1, 2, and/or 9 are involved in evoked neurotransmitter release (Sollner, 2003;Rizo & Sudhof, 1998).…”
Section: Modulation Of Excitatory and Inhibitory Presynaptic Terminalmentioning
confidence: 52%
“…In the presence of Ca channel blockers Koyama et al, 1999;Shoudai et al, 2007) or in nominal Ca-free solution (Maeda et al, 2009), glycinergic sIPSC frequency decreases 30 ~40% of control. A large proportion of these TTX-resistant miniature IPSCs (mIPSCs) are independent from Ca 2+ influx (Emptage et al, 2001;Miller et al, 1998;Scholtz et al, 1992), as reported by others.…”
Section: General Properties Of Spontaneous and Evoked Transmitter Relmentioning
confidence: 96%
“…Stimuli that failed to evoke a response (i.e., current amplitude ¼ 0) were referred to as failures and used to calculate the failure rate (Rf). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 depend on the amount of Ca 2þ influx into the presynaptic terminal (Maeda et al, 2009), and furthermore amplitude could be modulated by the sensitivity of syn...…”
Section: Discussionmentioning
confidence: 99%